Systemic risk and CO2 emissions in the U.S. - Kanas, Angelos; Molyneux, Philip; Zervopoulos, Panagiotis D. (Journal of Financial Stability, 2023)
We provide both a theoretical framework and empirical results for the relationship between CO2 emissions and systemic risk in the U.S. Based on a modified structural distance-to-default model that integrates physical risk effects, a theoretical framework is developed, documenting a positive link between CO2 emissions and systemic risk. Network VAR analysis, Diebold and Yilmaz variance decomposition, and conditional Granger causality provide empirical support for this positive link. Bank assets are found to be negatively related to CO2 emissions, which indicates an adjustment of the banking sector’s assets towards a lower-carbon economy. Policy implications include government-sponsored insurance support for banks facing insured losses.